Non-Compliance Dietary Factors in diabetic mellitus Clients - Ubaidillah, Zaqqi (Journal of Borneo Holistic Health, 2019)
Background : Diabetes Mellitus (DM) is a chronic disease increase significantly every year. One of the difficulties in managing diabetes mellitus is the non-compliance of the diet and it cause uncontrolled and unstable glucose. Purpose : To identify non-compliance of diabetic mellitus dietary factors in Saptorenggo and Pakisjajar in District Pakis Malang. Method : A design study used descriptive. This study was already held in 10-16 September 2018 at Saptorenggo and Pakisjajar. The number of sample were 37 respondent and used to total sampling method. The data collection technique used questionnaire. Result : Results of the research on the non-compliance of diabetic mellitus dietary factors, the majority of respondents had a late adult age range of 16 people or 43.24%. On economic factors, in terms of the income of respondents with income below the basic standard salary, 18 people or 37.84%. From the family support factor, 25 people or 67.57% have a low level. Whereas from the knowledge of diabetes mellitus dietary factor with a total of 23 people or 62.16% have good enough. Conclusion : Majority of respondent reveal if amount of salary be related with education capability and family support is non-compliance diabetic mellitus dietary factors.Â Â  Keywords: Non-compliance dieabetic mellitus dietary factor, Diabetic Mellitus, Family Support